2020
DOI: 10.3390/app10051782
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Characteristics of Single- and Joggled-Lap CFRP Specimens: Mechanical and Acoustic Investigations

Abstract: Two different configurations of adhesive-bonded carbon fiber-reinforced plastic (CFRP) specimens, joggled lap-joint specimens and single lap-joint specimens, are mechanically tested. The mechanical tests show that the joggled lap specimens have lower strength than the single lap specimens. The damage modes in both the specimens are analysed by the Acoustic Emission descriptors recorded during the mechanical tests. The acoustic data as cumulative counts and cumulative energy show the critical points of failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This distinction is made since in the static tests the displacement increases constantly and has no direct influence. For this reason, any drop in force corresponds to a change in the stiffness of the specimen caused by glass fibre breakage or delamination as it has been shown in [ 39 , 42 , 44 , 47 ]. In contrast, the displacement and force changes cyclically in the dynamic tests, so the ratio of both should be constant over time.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This distinction is made since in the static tests the displacement increases constantly and has no direct influence. For this reason, any drop in force corresponds to a change in the stiffness of the specimen caused by glass fibre breakage or delamination as it has been shown in [ 39 , 42 , 44 , 47 ]. In contrast, the displacement and force changes cyclically in the dynamic tests, so the ratio of both should be constant over time.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in both cases the time can be determined by applying the threshold technique, only the determination of the healthy state and the corresponding reference value must be determined for each individual laminate. In summery, the complete failure detection in static test scenarios is going hand in hand with the results of the literature using carbon fibre-reinforced plastic [ 39 , 42 , 43 , 44 ], while the dynamic results going along with the results from Saeedifar et.al [ 45 ]. Consequently, the hypotheses H1 and H4 are confirmed, as it has been sufficiently demonstrated that both the damage index I and the standard deviation of the SED are applicable to determine the time of complete failure.…”
Section: Discussionmentioning
confidence: 99%
“…The acoustic waves generated during the straining and failure modes propagate in two different modes as mentioned in Section 2.4. The lower order symmetric AE signals, which represent the matrix cracking or interfacial failure normally has large number of counts [14,25]. The accumulation of these damages before the specimens loses their load carrying capacity is the reason for the rapid increase in the cumulative counts before the failure.…”
Section: Cumulative Countsmentioning
confidence: 99%
“…The AE descriptors, total number of hits or events, counts, acoustic energy, peak frequency/ amplitude are commonly used by researchers to identify/predict the damage propagation or initiation in a material. More details about the different AE descriptors and their applications can be found elsewhere [14,15]. The definitions of the AE descriptors considered for this study are provided in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are various candidates for the main fabrics used for carbon composite materials, such as plain weave, twill weave, and unidirectional, and thus there are various laminated structures in which these are combined. Therefore, in order to utilize the carbon composite material in products, it should be noted that the mechanical properties basically vary depending on the laminated structure, and the test results necessarily vary as well [10][11][12].…”
Section: Introductionmentioning
confidence: 99%